Adaptive reuse of cultural built heritage: towards the implementation of the circular city model - Angrisano, M.; Bottero, M.; Cavana, G.; Fabbrocino, F.; Gravagnuolo, A.; Fusco Girard, L. (Frontiers in Built Environment, 2025)
Climate change, pollution, and inequalities are prominent issues in cities and regions, calling for an ecological and cultural transition towards a sustainable society where wellbeing, quality of life, ecosystems human health and equity are prioritized. Circular economy and circular city models offer frameworks for achieving these objectives, promoting symbiotic relationships between different forms of capital within urban ecosystems: economic, environmental, social, cultural, institutional and human capitals. Historic urban areas, through the adaptive reuse of cultural heritage, can contribute to the circular economy model, enhancing urban metabolism while preserving cultural integrity. Co-design and co-planning processes involving stakeholders and communities are essential to realize the circular city, thus integrating conservation with development. The aim of this paper is to conduct an ex post analysis of cultural heritage adaptive reuse projects in Europe, that are particularly well “performing” from the perspective of the circular economy implementation in cities and regions. Circular economy is interpreted not only in terms of reuse/regeneration of waste, but also has promoting a new mindset. These examples are examined based on specific criteria and indicators from the EU-funded Horizon 2020 CLIC research project, identifying success factors, tools, and models emerging from good practices that can potentially be replicated and transferred for the circular adaptive reuse of Italian cultural heritage. Particular attention in the selection of case studies has been given to the co-planning and co-design experiences activated, to highlight the social innovation capacity of the analysed adaptive reuse projects.